Placental magnetic resonance imaging in chronic hypertension: A case-control study. (15th January 2021) - Ho, Alison; Hutter, Jana; Slator, Paddy; Jackson, Laurence; Seed, Paul T.; Mccabe, Laura; Al-Adnani, Mudher; Marnerides, Andreas; George, Simi; Story, Lisa; Hajnal, Joseph V.; Rutherford, Mary; et al.
Abstract: Introduction: We aimed to explore the use of magnetic resonance imaging (MRI) in vivo as a tool to elucidate the placental phenotype in women with chronic hypertension. Methods: In case-control study, women with chronic hypertension and those with uncomplicated pregnancies were imaged using either a 3T Achieva or 1.5T Ingenia scanner. T2-weighted images, diffusion weighted and T1/T2* relaxometry data was acquired. Placental T2*, T1 and apparent diffusion coefficient (ADC) maps were calculated. Results: 129 women (43 with chronic hypertension and 86 uncomplicated pregnancies) were imaged at a median of 27.7 weeks' gestation (interquartile range (IQR) 23.9–32.1) and 28.9 (IQR 26.1–32.9) respectively. Visual analysis of T2-weighted imaging demonstrated placentae to be either appropriate for gestation or to have advanced lobulation in women with chronic hypertension, resulting in a greater range of placental mean T2* values for a given gestation, compared to gestation-matched controls. Both skew and kurtosis (derived from histograms of T2* values across the whole placenta) increased with advancing gestational age at imaging in healthy pregnancies; women with chronic hypertension had values overlapping those in the control group range. Upon visual assessment, the mean ADC declined in the third trimester, with a corresponding decline in placental mean T2* values and showed an overlap of values between women with chronic hypertension and the control group. Discussion: A combined placental MR examination including T2 weighted imaging, T2*, T1 mapping and diffusion imaging demonstrates varying placental phenotypes in a cohort of women with chronic hypertension, showing overlap with the control group. Highlights: MRI enables evaluation of the placental contribution of adverse pregnancy outcomes. Placental MRI examination was undertaken in women with chronic hypertension. T2-weighted imaging showed varied placental visual appearance compared to controls. Overlap in mean T2*, T1, ADC and T2* histogram derived measures was noted. MRI may elucidate placental dysfunction and development of adverse outcomes.